Lee Lozano - Müller-Westermann, Iris; Applin, Jo; Lippard, Lucy; Meyer-Krahmer, Benjamin (Ostfildern, Stockholm : Hatje Cantz, Moderna Museet, 2010)
"Making art is the greatest act of all" : Lee Lozano's investigations / Iris Müller-Westermann ## How to do things with script : the art of Lee Lozano's language and writing / Benjamin Meyer-Krahmer ## Lozano's labor / Jo Applin ## Cerebellion and cosmic storms / Lucy R. Lippard.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Lozano, Lee